2018
DOI: 10.3389/fphys.2018.00806
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress: A Major Player in Cerebrovascular Alterations Associated to Neurodegenerative Events

Abstract: The brain is one of the most exquisite organs in the body with high metabolic demands, and requires a tight regulation of the surrounding environment. This tight control is exerted by the neurovascular unit (NVU) comprising different cell types, where endothelial cells play the commander-in-chief role. Thus, it is assumable that even slight perturbations in NVU might affect, in some cases irreversibly, brain homeostasis and health. In this line, recent findings support the two-hit vascular hypothesis for neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
112
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 176 publications
(215 reference statements)
0
112
0
Order By: Relevance
“…However, in a disease state, the integrity of this barrier may be affected, allowing hormonal RAS components entry into the cerebral regions, especially the cardiovascular regulatory areas (Palmer et al, 2013). Studies have shown that brain RAS triggers chronic inflammation leading to the release of ROS and inflammatory mediators through activating glial cells (Carvalho and Moreira, 2018). Uncontrolled effects of these mediators upregulate various inflammatory cascades resulting in cognitive dysfunction and neurodegeneration (Sun et al, 2018;Martire et al, 2015).…”
Section: Neuro-inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in a disease state, the integrity of this barrier may be affected, allowing hormonal RAS components entry into the cerebral regions, especially the cardiovascular regulatory areas (Palmer et al, 2013). Studies have shown that brain RAS triggers chronic inflammation leading to the release of ROS and inflammatory mediators through activating glial cells (Carvalho and Moreira, 2018). Uncontrolled effects of these mediators upregulate various inflammatory cascades resulting in cognitive dysfunction and neurodegeneration (Sun et al, 2018;Martire et al, 2015).…”
Section: Neuro-inflammationmentioning
confidence: 99%
“…In a recent review, O'Connor and colleagues reported that excessive ang II generated due to astrocyte dysfunction resulted in neuroinflammation and loss of neuronal activity (Amin et al, 2016). In Addition, inflammation and other abnormal neurovascular alterations resulting from the effect of RAS along the AT1R axis have been linked to AD, although detailed mechanisms are still elusive (Carvalho and Moreira, 2018). Ang II treatment of mesencephalic cultures, caused activation of the microglial RhoA/ROCK pathway and the upregulation of microglia tumor necrotic factor, TNF a, a proinflammatory cytokine that facilitate dopaminergic neurodegeneration Saavedra, 2012).…”
Section: Neuro-inflammationmentioning
confidence: 99%
“…Oxidative, nitrosative stress and inflammation in neuron can cause dysfunction of neural junction, and then induce the nervous system damage. 36 The antioxidant enzymes were significantly decreased in AD mice. 37,38 In this study, the primary indicators of oxidative and nitrosative stress were obviously increased after IL-1β, IL-6 and TNF-α, were observed in AD brain.…”
Section: Discussionmentioning
confidence: 97%
“…Oxidative, nitrosative stress and inflammation are playing crucial roles in cell homeostasis and apoptosis. Oxidative, nitrosative stress and inflammation in neuron can cause dysfunction of neural junction, and then induce the nervous system damage . The antioxidant enzymes were significantly decreased in AD mice .…”
Section: Discussionmentioning
confidence: 99%
“…The blood-brain barrier (BBB) neuro vascular unit (NVU), made up of neurons, astrocytes, pericytes, microglia and endothelial cells, can counteract the effects of oxidation when the amount of ROS is limited and when the activity of antioxidant enzymes is preserved. Any imbalance in the NVU functioning may alter the brain homeostasis, resulting in high oxidative stress and the impairment of the integrity of the BBB [14,15].…”
Section: Oxidative Metabolism In Neurodegenerative Diseasesmentioning
confidence: 99%